1999
DOI: 10.1021/jm991005d
|View full text |Cite
|
Sign up to set email alerts
|

New (Sulfonyloxy)piperazinyldibenzazepines as Potential Atypical Antipsychotics:  Chemistry and Pharmacological Evaluation

Abstract: A series of 2- or 8-trifluoromethylsulfonyloxy (TfO) and 2- or 8-methylsulfonyloxy (MsO) 11-piperazinyldibenzodiazepines, -oxazepines, and -thiazepines were synthesized and evaluated in pharmacological models for their potential clozapine-like properties. In receptor binding assays, the 2-TfO analogues (18a, GMC2-83; 24, GMC3-06; and previously reported GMC1-169, 9a) of the dibenzazepines have profiles comparable to that of clozapine, acting on a variety of CNS receptors except they lack M1 receptor affinity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 44 publications
0
91
0
Order By: Relevance
“…36,37 Other variations have been reported. 38,39 For example, the original patent also describes coupling Nmethylpiperazine to 13 to generate the corresponding amide prior to thermal condensation leading to 3 directly. En route to a tritiated version of 3, de Paulis and co-workers 39 first converted 14 to the thioamide, followed by methylation to provide an alternate leaving group for displacement by the tritiated N-methylpiperazine.…”
Section: ■ Chemical Synthesismentioning
confidence: 99%
“…36,37 Other variations have been reported. 38,39 For example, the original patent also describes coupling Nmethylpiperazine to 13 to generate the corresponding amide prior to thermal condensation leading to 3 directly. En route to a tritiated version of 3, de Paulis and co-workers 39 first converted 14 to the thioamide, followed by methylation to provide an alternate leaving group for displacement by the tritiated N-methylpiperazine.…”
Section: ■ Chemical Synthesismentioning
confidence: 99%
“…The other regioisomer 2-aryl-2,3-dihydronaphto[1,2-f] [1,4]oxazepin-4(1H)-ones 8a-c, which could be formed from the nitrogen attack, were not isolated. …”
Section: Scheme 1 Synthesis Of Naphthoxazepines 7a-cmentioning
confidence: 99%
“…5,6 Additionally, benzo [1,4]oxazepines are crucial moieties in many psychoactive drugs. 7,8 It was found that dibenzo[b,f] [1,4]oxazepin-11(10H)-ones to be selective inhibitors of human immunodefiency virus (HIV) type 1 reverse transcriptase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Most syntheses of 2,3,4,5-tetrahydro-1,4-benzoxazepines involve the reduction of the carbonyl group(s) as for 5-oxo-2,3,4,5-tetrahydro-1,4-benzoxazepine, 3-oxo-2,3,4,5-tetrahydro-1,4-benzoxazepine, and 3,5-dioxo-2,3,4,5-tetrahydro-1,4-benzoxazepine, or the reduction of a double bond as for 2,3-dihydro-1,4-benzoxazepine. 1,[6][7][8] Alternatively, 2,3,4,5-tetrahydro-1,4-benzoxazepines are accessible by one of the following known benzoxazepine syntheses: (i) condensation of 2-aryloxyethylamines with 2-formylbenzoic acid to form aminonaphthalides followed by cyclization: (ii) rearrangement of methyl 2-(8-methoxy-2,3-dihydro-1,4-benzoxazepin-5-yl)benzoate using Bischler-Napieralski conditions; (iii) scandium or copper triflate-catalyzed acylaminoalkylation of α-methoxy-isoindolones with the formation of 1,4-benzoxazepines.…”
Section: Introductionmentioning
confidence: 99%